Pembelajaran Berkarakter dalam Masyarakat Ekonomi Asean (MEA) - Isyatul Mardiyati (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2016)
In the middle of technology advances, transportation and communication. Various south east asia country is facing crisis of cultural values of nationalities identity, this issue not only make a nation loses dignity as an independent, this even prediction to born a new universal identity that dull the old characters.As a framework to fortify young generations from globalization development that eroded cultural values character of nation, hopefully characters learning is an alternative way to face various kinds of multi demention problem faced by Indonesian and southeast asia.